2018
DOI: 10.1080/02699052.2018.1497203
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time on cognitive impairments after non-traumatic subarachnoid haemorrhage and after traumatic brain injury

Abstract: Cognitive improvements after SAH and TBI exhibit similarities and correlate with global function. GCS scores are associated with outcome after TBI but not after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The most common hypofunction in the current study group was for gonadal hormones, observed in 38%, and most common hyperfunction for high cortisol levels in 52% (Table II). As recently reported (19), although both cognitive and global function improves significantly until 12 months after both TBI and aSAH, impairments remain at 12 months. In the current study group, cognitive impairment according to BNIS was present in 54% of cases and impaired global outcome according to GOSE in 37%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The most common hypofunction in the current study group was for gonadal hormones, observed in 38%, and most common hyperfunction for high cortisol levels in 52% (Table II). As recently reported (19), although both cognitive and global function improves significantly until 12 months after both TBI and aSAH, impairments remain at 12 months. In the current study group, cognitive impairment according to BNIS was present in 54% of cases and impaired global outcome according to GOSE in 37%.…”
Section: Discussionsupporting
confidence: 80%
“…Most PiDs were transient, with no need for replacement therapy, but a small subgroup (7%) needed such therapy. In this cohort of patients, who were recruited from the neurointensive care unit at one university hospital and who went through the same structured neurorehabilitation and follow-up programme, we also assessed cognitive and global function until one year after the event (19). Cognitive and global function improved significantly over time in both diagnostic groups and was not significantly different between groups at 12 months.…”
mentioning
confidence: 99%
“…64 On the contrary, five studies (n=261) found no change in depressive symptoms between the first assessment at 3, 6, or 9 months and subsequent follow-up(s) at 6, 9 months, 1, 1.5, 2, or 4 years after SAH. 18,19,23,25,29 In a cross-sectional study, the proportion of patients with depression was not statistically different from patients 2 to 5, 5 to 10, and even more than 10 years after SAH, with 8.3%, 10.7%, and 8.6%, respectively. 37 The weighted frequency of depression was 33% up to a year after SAH and 28% a year or more after.…”
Section: Time Course Of Depression After Sahmentioning
confidence: 84%
“…Fifty-one of 55 studies (93%) used one of the following screening or rating scales to ascertain the presence of depression: Hospital Anxiety Depression Scale (HADS), 18,19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Beck Depression Inventory (BDI), [12][13][14][15][16][17][18][19][20][21][40][41][42][43][44][45][46][47][48][49][50][51] Center for Epidemiologic Studies Depression (CESD), [22][23][24]52,53 Montgomery Åsberg Depression Rating Scale (MADRS), 54,55 Geriatric Depression Scale (GDS), 56,57 International Classification of Diseases...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation